2002
DOI: 10.1007/s11664-002-0003-0
|View full text |Cite
|
Sign up to set email alerts
|

Experimental determination and thermodynamic calculation of the phase equilibria and surface tension in the Sn-Ag-In system

Abstract: The phase equilibria of the Sn-Ag-In system were investigated by means of differential scanning calorimetry (DSC) and metallography. The isothermal sections at 180-600°C, as well as some vertical sections, were determined. Thermodynamic assessment of this system was also carried out based on the experimental data of thermodynamic properties and phase equilibria using the calculation of phase diagram (CALPHAD) method, in which the Gibbs energies of the liquid, fcc, and hcp phases are described by the subregular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
65
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 21 publications
5
65
0
1
Order By: Relevance
“…pct Cu on a Cu substrate was the largest at 823 K (550°C). These tests also showed that the temperature affects of the formation and growth of some intermetallic phases, such as Cu 5 2 and Al approximately 300 mm 2 ). The melting point of Cu is higher than that of Al, which results in the formation of IMPs in the Cu-Zn system and the dissolution of Al in the Al-Zn system, as shown by the phase diagram.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…pct Cu on a Cu substrate was the largest at 823 K (550°C). These tests also showed that the temperature affects of the formation and growth of some intermetallic phases, such as Cu 5 2 and Al approximately 300 mm 2 ). The melting point of Cu is higher than that of Al, which results in the formation of IMPs in the Cu-Zn system and the dissolution of Al in the Al-Zn system, as shown by the phase diagram.…”
Section: Discussionmentioning
confidence: 88%
“…The electrical and electronics industries have developed replacements using the addition of alloying elements to lead-free and tin-based soft solder that melts at 503 K (230°C). [1][2][3][4][5] However, the automotive and cooling industries have used solders with higher melting points. [6] Therefore, an important task is to develop new solders with appropriate wetting properties, melting points, mechanical strength, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of such trends were published jointly in the case of Ag-In 1) and Sn-Ag-In 2) liquid alloys. The separate experimental studies 3) in Krakow on surface tension and density on binary low melting eutectics and on third additions to binary eutectics have shown that the comparison of the surface tension with the values calculated from optimized thermodynamic parameters is reliable.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al, 2001c); (Moser, Gąsior & Pstruś, 2001b); (Gąsior, Moser, & Pstruś, 2003a); (Moser, Gąsior, Ishida, Ohnuma, Liu, Bukat et al, 2005b); (Pamies, Garcia-Cordovilla & Louis, 1984) (Nogi, Oishi & Ogino, 1989); (Gąsior, Moser & Dębski, 2004c); (Liu, Inohana, Ohnuma, Kainuma, Ishida, Moseret al, 2002); (Gąsior, Moser, Pstruś, Krzyżak & Fitzner, 2003b); ; (Moser, Gąsior & Pstruś, 2005a); (Gąsior, Moser, Pstruś, Bukat, Kisiel & Sitek, 2004e); (Moser, Gąsior, Pstruś & Księżarek, 2002); (Moser, Gąsior, Pstruś, Ishihara, Liu, Ohnuma et al, 2004d); (Gąsior, Moser & Pstruś, 2004b); (Moser, Gąsior, Ishida, Ohnuma, Bukat, Pstruś et al, 2004c); (Gąsior, Moser, Bukat, Pstrus, Sitek, & Kisiel, 2004d); (Kisiel, Gąsior, Moser, Pstruś, Bukat & Sitek, 2005). (Gąsior et al, 2001) Pb -Sn (Gąsior et al, 2001) (Sn-Ag) eut +Zn * Sn (Moser et al, 2001a) Ag -Sn (Moser et al, 2001a) (Sn-Ag) eut +In (Liu et al, 2002) In (Moser et al, 2001c) Ag -In (Moser et al, 2001c) (Sn-Ag) eut +Bi (Moser et al, 2001b) Ag (Moser et al, 2001c) Bi -Sn ) (Moser et al, 2001b) (Sn-Ag) eut +Cu (Gąsior et al, 2004e) ) Bi (Moser et al, 2001b) In -Sn (Liu et al, 2002) (Sn-Ag) eut +Sb Sb (Gąsior et al, 2003a) Ag -Bi (Gąsior et al, 2003b) (Sn-Ag) eut +Cu+Sb (Moser et al, 2005a) Cu (Moser et al, 2005b) Sb -Sn (Gąsior et al, 2003a) (Sn-Ag) eut +Cu+Bi (Moser et al, 2005b) ) Zn * In -Zn Sn -Zn A...…”
Section: Introductionunclassified
“…This co-operation was next extended on phase diagram calculation (Moser et al, 2001c;Liu et al, 2002) and on simulation of solidification. The enclosed two schemes dealing with the ADAMIS and SURDAT data bases show the structures and the main functioning of both data bases Gąsior, Moser & Dębski, 2004a).…”
Section: Introductionmentioning
confidence: 99%